Flow battery proton exchange membrane and preparation method thereof
Crosslinked proton exchange membranes were prepared by interfacial polymerization and ultraviolet light irradiation, which solved the problems of low proton conductivity and high preparation cost of proton exchange membranes in flow batteries. This method enables the preparation of high-performance and low-cost proton exchange membranes, which are applicable to various flow battery types, including all-vanadium redox flow batteries.
Patent Information
- Application Number
- CN202511320205.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-12
AI Technical Summary
Existing proton exchange membranes for flow batteries suffer from low proton conductivity, poor ion selectivity, and high manufacturing costs. In particular, the vanadium ion permeability of Nafion series membranes is a significant problem, which restricts their large-scale application.
By performing interfacial polymerization on the surface of a substrate material to form a cross-linked proton exchange membrane, and combining ultraviolet light irradiation and hydrophilic polymer treatment, a proton exchange membrane with high proton conductivity, thin functional skin, and low cost can be prepared.
It improves proton conduction performance, enhances the chemical and physical stability of the membrane, and reduces preparation costs, making it suitable for industrial production.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of proton exchange membrane, in particular to a kind of liquid flow battery proton exchange membrane and preparation method thereof. BACKGROUND
[0002] The current human demand for energy is rising with the rapid growth of the global economy. However, the increasing depletion of global fossil fuel resources and the intensification of environmental pollution have led to the inability to rely on fossil fuels to maintain the development of the national economy. Therefore, the development of renewable energy and energy storage technology is imminent. Among the many energy storage technologies, liquid flow batteries have attracted widespread attention from countries around the world due to their long life, high capacity, and independence from power design.
[0003] Liquid flow batteries are mainly composed of electrolyte, electrode, selective proton exchange membrane, bipolar plate and current collector. Among them, the proton exchange membrane is one of the key components of the liquid flow battery, and its performance directly affects the performance and service life of the battery. It should meet high proton conductivity, high ion selectivity, excellent physical and chemical stability, and low price. At present, the proton exchange membrane used in liquid flow batteries is mainly perfluorinated membrane (such as DuPont's Nafion series membrane) and non-fluorinated membrane. Perfluorinated membranes have high proton conductivity, but the vanadium ion permeability problem is more prominent, and the ion selectivity is poor. In addition, the preparation cost of Nafion series membrane is high, which is also a key factor restricting the large-scale application of Nafion series membrane in liquid flow batteries.
[0004] In the past decade, researchers have found that polyether ether ketone, polybenzimidazole and polyimide polymers have strong conduction capacity and good mechanical properties, and have broad application prospects in liquid flow batteries. These non-fluorinated polymer membranes are prepared by dissolving the polymer into a film and then post-processing. Compared with perfluorinated membranes, non-fluorinated membranes are cheaper, simpler to prepare, and have a shorter process flow. However, the polymer membranes must be protonated by strong acid to improve the proton conductivity, and the proton conductivity is poor. SUMMARY
[0005] The purpose of the present application is to provide a liquid flow battery proton exchange membrane, which has high proton conductivity, thin functional skin layer and low preparation cost.
[0006] The proton exchange membrane of the present application is prepared by sequentially immersing the base material in an aqueous solution and an organic phase solution, forming a thin skin layer by interfacial polymerization, and then irradiating it with ultraviolet light and post-processing.
[0007] Another purpose of the present application is to provide a preparation method for a liquid flow battery proton exchange membrane, which has a short process flow, low cost, simple raw materials and is easy to realize industrial production.
[0008] To achieve the above object, the application provides a preparation method of a proton exchange membrane of a liquid flow battery, which comprises the following steps: S1, preparing an aqueous phase solution by mixing 3,3'-diamino-benzidine, a zinc salt and water; S2, preparing an organic phase solution by mixing an organic phase monomer, an initiator, an additive and a solvent; S3, applying the aqueous phase solution to the surface of a substrate material, and removing the excess aqueous phase solution; S4, applying the organic phase solution to the surface of the substrate material again, removing the excess organic phase solution, and drying to form a skin layer film; S5, irradiating the skin layer film with ultraviolet light to form a cross-linked proton exchange membrane; S6, placing a hydrophilic polymer aqueous solution on the surface of the cross-linked proton exchange membrane, and drying to form a functional layer.
[0009] According to the application, the zinc salt in step S1 is zinc nitrate or zinc acetate.
[0010] According to the application, the content of the 3,3'-diamino-benzidine in the aqueous phase solution in step S1 is 0.5-10wt%.
[0011] According to the application, the molar ratio of the zinc salt to the 3,3'-diamino-benzidine in step S1 is 1:1-5.
[0012] According to the application, the organic phase monomer in step S2 is a mixture of a polyaldehyde and a polyacyl chloride.
[0013] Further, the polyaldehyde is malondialdehyde, butanedialdehyde, pentanedialdehyde, hexanedialdehyde or heptanedialdehyde.
[0014] Further, the polyacyl chloride is trimesyl chloride, benzenesulfonyl chloride or cyanuric chloride.
[0015] Further, the molar ratio of the polyaldehyde to the polyacyl chloride is 1:9-9:1.
[0016] According to the application, the content of the organic phase monomer in the organic phase solution in step S2 is 0.01-5wt%.
[0017] According to the application, the initiator in step S2 is benzophenone, phenylethanone, benzoin, benzoin ether, benzil or benzil ketal.
[0018] According to the application, the content of the initiator in the organic phase solution in step S2 is 0.005-1wt%.
[0019] According to the application, the additive in step S2 is 2-methylimidazole, benzimidazole or benzotriazole.
[0020] According to the present application, the molar ratio of the additive in step S2 to the zinc salt in step S1 is 2-6:1.
[0021] According to the present application, the solvent in step S2 is n-hexane, cyclohexane, n-heptane or isomeric alkanes.
[0022] According to the present application, the base material in step S3 is glass fiber, non-woven fabric, sulfonated polyether ether ketone membrane, polyvinylidene fluoride membrane or polytetrafluoroethylene membrane.
[0023] Further, the material of the non-woven fabric can be polypropylene, polyethylene or polyether ether ketone.
[0024] According to the present application, the time for applying the aqueous solution in step S3 is 20-600 s.
[0025] Preferably, the time for applying the aqueous solution is 30-200 s.
[0026] According to the present application, the time for applying the organic phase solution in step S4 is 20-600 s.
[0027] Preferably, the time for applying the organic phase solution is 30-200 s.
[0028] According to the present application, the drying condition in step S4 is a temperature of 60-100℃ and a time of 2-10 min.
[0029] According to the present application, the ultraviolet light irradiation in step S5 uses an ultraviolet lamp, and the irradiation time is 5-60 min.
[0030] According to the present application, the hydrophilic polymer in step S6 is polyvinyl alcohol, polyethyleneimine, chitosan or chitosan quaternary ammonium salt.
[0031] Further, the content of the hydrophilic polymer is 0.01-20 wt%.
[0032] Preferably, the content of the hydrophilic polymer is 0.1-10 wt%.
[0033] According to the present application, the time for treating the hydrophilic polymer aqueous solution in step S6 is 2-60 min.
[0034] According to the present application, the drying condition in step S6 is a temperature of 80-100℃ and a time of 2-10 min.
[0035] Another object of the present application is to provide the application of the liquid flow battery proton exchange membrane in a full vanadium liquid flow battery, iron / chromium liquid flow battery, zinc / bromine liquid flow battery, sulfur / bromine liquid flow battery, sulfur / iron liquid flow battery, vanadium / bromine liquid flow battery or vanadium / iron liquid flow battery. Compared with the prior art, the present application has the following advantages:
[0036] 1) The present application carries out interfacial polymerization reaction of 3,3'-diaminobiphenyl and organic phase monomers on the surface of a base material, and forms a cross-linked proton exchange membrane by ultraviolet irradiation. The proton exchange membrane has a thin separation layer and is resistant to acid and alkali and has good chemical reagent stability.
[0037] 2) The present application adds metal ions and organic ligands of a metal organic framework material into an aqueous solution and an organic solution respectively. In the interfacial polymerization, a skin layer film and a metal organic framework material can be formed at the same time, so that the metal organic framework material is uniformly distributed in the skin layer film, a channel is provided for proton transmission of the proton exchange membrane, and the proton conduction performance is improved.
[0038] 3) The hydrophilic polymer used in the present application can react with unreacted acyl chloride or aldehyde groups remaining on the surface of the skin layer film to form a molecular level hydrophilic functional layer, further improve the hydrophilicity of the membrane surface, change the chemical structure, promote proton transfer, and significantly improve the proton conductivity. DETAILED DESCRIPTION Example 1
[0039] 0.1g of 3,3'-diaminobiphenyl, 0.09g of zinc nitrate and 19.81g of water are weighed to form an aqueous solution; 0.0015g of trimesoyl chloride, 0.0005g of butanedial, 0.001g of benzoin, 0.078g of 2-methylimidazole and 19.919g of cyclohexane are weighed to form an organic solution; the above aqueous solution is applied to the surface of a sulfonated polyether ether ketone membrane, and the sulfonated polyether ether ketone membrane is taken out after 200s, and the surface thereof is blown dry with nitrogen; the above organic solution is applied to the surface of the sulfonated polyether ether ketone membrane, and the sulfonated polyether ether ketone membrane is taken out after 200s and placed in a 60℃ oven for 10min to form a skin layer film; the skin layer film is irradiated under a UV lamp for 40min to form a cross-linked proton exchange membrane; the membrane is placed in 100g of a polyvinyl alcohol aqueous solution (0.1g of polyvinyl alcohol and 99.9g of water), taken out after 10min and dried at 80℃ for 8min to obtain a proton exchange membrane for a flow battery. Example 2
[0040] Take 1.2 g of 3,3'-diaminobenzidine, 0.5 g of zinc acetate and 18.3 g of water to form an aqueous phase solution; take 0.0575 g of cyanuric chloride, 0.1425 g of adipaldehyde, 0.01 g of benzophenone, 0.97 g of benzimidazole and 18.82 g of n-hexane to form an organic phase solution; apply the above aqueous phase solution to the surface of the glass fiber graphite felt, take out the glass fiber graphite felt after 150 s, and blow dry the surface with nitrogen; then apply the above organic phase solution to the surface of the glass fiber graphite felt, take out the glass fiber graphite felt after 150 s, and place it in a 70°C oven for 8 min to form a skin film; irradiate the skin film under a UV lamp for 60 min to form a cross-linked proton exchange membrane; place the membrane in 100 g of a chitosan aqueous solution (1 g of chitosan, 99 g of water), and take it out after 60 min and dry it at 90°C for 5 min to obtain a proton exchange membrane for a flow battery. Example 3
[0041] Take 2 g of 3,3'-diaminobenzidine, 0.6 g of zinc nitrate and 17.4 g of water to form an aqueous phase solution; take 0.216 g of benzenesulfonyl chloride, 0.184 g of glutaraldehyde, 0.002 g of benzoyl, 2.267 g of benzotriazole and 17.331 g of cyclohexane to form an organic phase solution; apply the above aqueous phase solution to the surface of the polytetrafluoroethylene film, take out the polytetrafluoroethylene film after 120 s, and blow dry the surface with nitrogen; then apply the above organic phase solution to the surface of the polytetrafluoroethylene film, take out the polytetrafluoroethylene film after 120 s, and place it in a 100°C oven for 2 min to form a skin film; irradiate the skin film under a UV lamp for 30 min to form a cross-linked proton exchange membrane; place the membrane in 100 g of a polyethyleneimine aqueous solution (10 g of polyethyleneimine, 90 g of water), and take it out after 2 min and dry it at 80°C for 10 min to obtain a proton exchange membrane for a flow battery. Example 4
[0042] Take 0.8 g of 3,3'-diaminobenzidine, 0.13 g of zinc acetate and 19.06 g of water to form an aqueous phase solution; take 0.2 g of trimesoyl chloride, 0.8 g of propanedial, 0.1 g of phenylethanone, 0.2 g of 2-methylimidazole and 18.61 g of Isopar G to form an organic phase solution; apply the above aqueous phase solution to the surface of the polypropylene non-woven fabric, take out the polypropylene non-woven fabric after 30 s, and blow dry the surface with nitrogen; then apply the above organic phase solution to the surface of the polypropylene non-woven fabric, take out the polypropylene non-woven fabric after 30 s, and place it in an 80°C oven for 5 min to form a skin film; irradiate the skin film under a UV lamp for 5 min to form a cross-linked proton exchange membrane; place the membrane in 100 g of a chitosan quaternary ammonium salt aqueous solution (5 g of chitosan quaternary ammonium salt, 95 g of water), and take it out after 30 min and dry it at 100°C for 2 min to obtain a proton exchange membrane for a flow battery.
[0043] Nafion 115 membrane commercially available was selected as the comparative membrane of the proton exchange membrane of the flow battery of the present application.
[0044] The proton exchange membranes of the flow battery prepared in Examples 1-4 of the present application were first protonated by 3M aqueous sulfuric acid solution for 7 days and then stored in deionized water for standby; the Nafion 115 membrane was soaked in 5wt% H2O2 solution, deionized water, 1mol•L-1 aqueous H2SO4 solution and deionized water respectively for 30min at a temperature of 80℃ and then stored in deionized water for standby. Then, the performance test of the all-vanadium flow battery was carried out respectively, and the results are as follows: -1 Table 1 Performance comparison of the all-vanadium flow battery of Examples 1-4 of the present application and the comparative example
Claims
1. A liquid flow battery proton exchange membrane, characterized in that, The skin layer film is prepared by immersing the base material in the aqueous solution and the organic solution in sequence, interfacial polymerization, UV irradiation and post-processing.
2. The liquid flow battery proton exchange membrane of claim 1, wherein, The base material is glass fiber, non-woven fabric, sulfonated polyether ether ketone membrane, polyvinylidene fluoride membrane or polytetrafluoroethylene membrane. Further, the non-woven fabric is made of polypropylene, polyethylene or polyether ether ketone.
3. The liquid flow battery proton exchange membrane of claim 1, wherein, The aqueous solution is composed of 3,3'-diaminobenzidine, zinc salt and water; the organic solution is composed of oily monomer, initiator, additive and solvent.
4. The method of making a proton exchange membrane for a flow battery of claim 1, wherein, The method comprises the following steps: S1: preparing an aqueous solution composed of 3,3'-diaminobenzidine, zinc salt and water; S2: preparing an organic solution composed of oily monomer, initiator, additive and solvent; S3: applying the aqueous solution to the surface of the base material and removing the excess aqueous solution; S4: applying the organic solution to the surface of the base material, removing the excess organic solution and drying to form a skin layer film; S5: irradiating the skin layer film with UV light to form a cross-linked proton exchange membrane; S6: placing a hydrophilic polymer aqueous solution on the surface of the cross-linked proton exchange membrane and drying to form a functional layer.
5. The preparation method according to claim 4, characterized in that, In step S1, the zinc salt is zinc nitrate or zinc acetate; in step S1, the molar ratio of the zinc salt to 3,3'-diaminobenzidine is 1:1-5; in step S1, the content of 3,3'-diaminobenzidine in the aqueous solution is 0.5-10wt%.
6. The preparation method according to claim 4, characterized in that, In step S2, the organic phase monomer is a mixture of polyaldehyde and polyacyl chloride; Further, the polyaldehyde is malondialdehyde, succinaldehyde, glutaraldehyde, adipaldehyde or pimelic aldehyde; Further, the polyacyl chloride is trimesyl chloride, benzenesulfonyl chloride or cyanuric chloride; Further, the molar ratio of the polyaldehyde to the polyacyl chloride is 1:9-9:1; In step S2, the content of the organic phase monomer in the organic solution is 0.01-5wt%; In step S2, the initiator is benzophenone, phenylacetone, benzoin, benzoin ether, benzil or benzil ketal; In step S2, the content of the initiator in the organic solution is 0.005-1wt%; In step S2, the additive is 2-methylimidazole, benzimidazole or benzotriazole; In step S2, the molar ratio of the additive to the zinc salt in step S1 is 2-6:1; In step S2, the solvent is n-hexane, cyclohexane, n-heptane or isomeric alkanes.
7. The preparation method according to claim 4, characterized in that, In step S3, the time for applying the aqueous solution is 20-600s; Preferably, the time for applying the aqueous solution is 30-200s; In step S4, the time for applying the organic solution is 20-600s; Preferably, the time for applying the organic solution is 30-200s; In step S4, the drying condition is: temperature 60-100℃, time 2-10min.
8. The preparation method according to claim 4, characterized in that, In step S5, the UV irradiation uses a UV lamp, and the irradiation time is 5-60min.
9. The preparation method according to claim 4, characterized in that, In step S6, the hydrophilic polymer is polyvinyl alcohol, polyethyleneimine, chitosan or chitosan quaternary ammonium salt; Further, the content of the hydrophilic polymer is 0.01-20wt%. Preferably, the content of the hydrophilic polymer is 0.1-10wt%; The time for treating the hydrophilic polymer aqueous solution in step S6 is 2-60min; The drying condition in step S6 is: temperature is 80-100℃, time is 2-10min.
10. Use of the proton exchange membrane of the flow battery as claimed in any one of claims 1-9 in a vanadium flow battery, an iron / chromium flow battery, a zinc / bromine flow battery, a sulfur / bromine flow battery, a sulfur / iron flow battery, a vanadium / bromine flow battery or a vanadium / iron flow battery.
Citation Information
Cited By
Flow battery capacity recovery system and method
CN121307115A